Music: a natural phenomenon or a cultural invention? A few remarks on the currency of the polemic and its musicological consequences - Podlipniak, Piotr (My University, 2009)
The question of musical naturalness has increasingly often been the subject of lively debates within both natural and human sciences. In the present paper the issue is discussed primarily in terms of the propositions which accord with the contemporary naturalistic vision of a human and the world. One of the most important problems in this context is the opposition between a natural phenomenon and a cultural invention. Among the vast amount of different human achievements, some demand strenuous learning whereas other emerge spontaneously in all societies. The latter type of achievements is the result of the natural selection of human abilities. Recently, it has been hotly debated whether or not music is a biological adaptation. If it is, musical abilities should give an important advantage to individuals. There are numerous examples of the possible advantages. Namely, the music abilities play an important role in the enhancement of bonding between the mother and her infant child. Moreover, they are salient in the indication of fitness during sexual display. The abilities are also vital in the consolidation of a group during social music performance as well as in the transmission of information about the stability and cohesion of the group. If musical abilities are indeed a vital form of adaptations, they may imply some further questions such as the existence of music-specific abilities and of musical universals, as well as the distinction between music understood as art and music understood as universal communication (like language). All these issues have different methodological consequences for the shape of musicology as a discipline of science. These are, among others, pre-empting Europocentrism in research, the possibilities and extension of the use of comparative methods in ethnomusicology, the scope and applicability of the interdisciplinary studies based on the reductional structure of knowledge.
Keywords: naturalism; evolution; cultural invention; adaptation; Mmusical universals; musical abilities; methodology of musicology; reductionism